2022
DOI: 10.1001/jamanetworkopen.2022.43799
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab vs Cyclophosphamide Induction Therapy for Patients With Granulomatosis With Polyangiitis

Abstract: ImportanceResults of randomized clinical trials have demonstrated rituximab’s noninferiority to cyclophosphamide as induction therapy for antineutrophil cytoplasm antibody (ANCA)–associated vasculitides (AAV), with neither treatment having a specific advantage for granulomatosis with polyangiitis (GPA). However, post hoc analysis results have suggested that rituximab might be more effective than cyclophosphamide in inducing remission in patients with proteinase 3–positive AAV.ObjectiveTo compare the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…We also investigated 2 secondary outcomes to explore the effects of rituximab‐ versus cyclophosphamide‐based treatment strategies on other clinically relevant outcomes in a real‐world setting. Similar to a recent retrospective cohort study conducted in France that analyzed outcomes in a smaller cohort of patients with mostly PR3‐ANCA+ AAV (33), we found that patients treated with rituximab were more likely to discontinue or achieve a lower dose of prednisone within 6 months of treatment initiation than patients treated with cyclophosphamide. Despite this observation, we found no difference in the risk of severe infection at 1, 2, and 5 years among those treated with rituximab‐ versus cyclophosphamide‐based strategies.…”
Section: Discussionsupporting
confidence: 84%
“…We also investigated 2 secondary outcomes to explore the effects of rituximab‐ versus cyclophosphamide‐based treatment strategies on other clinically relevant outcomes in a real‐world setting. Similar to a recent retrospective cohort study conducted in France that analyzed outcomes in a smaller cohort of patients with mostly PR3‐ANCA+ AAV (33), we found that patients treated with rituximab were more likely to discontinue or achieve a lower dose of prednisone within 6 months of treatment initiation than patients treated with cyclophosphamide. Despite this observation, we found no difference in the risk of severe infection at 1, 2, and 5 years among those treated with rituximab‐ versus cyclophosphamide‐based strategies.…”
Section: Discussionsupporting
confidence: 84%
“…IVCY, which can rapidly and directly damage broader pathogenic cells including T cells, macrophages and neutrophils infiltrating the kidney, may be more immediate and effective than RTX in the treatment of RPGN. The effectiveness of RTX and IVCY may differ depending on the AAV subtype and profile of activated lymphocytes; therefore, individualised consideration of patient background may be necessary for treatment selection in remission induction therapy of life-threatening AAV 30 31. Since this was a retrospective study using a nationwide administrative database, there was no novel information on the immunobiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another devastating and persistent systemic disease, granulomatosis with polyangiitis was traditionally managed by disease modulation with extended courses of high-dose CS and cytotoxic agents, which inconsistently induced remission and was associated with significant morbidity. 5,6 More recently, disease modulation has been replaced by highly effective disease modification achieved with B-cell depletion through the use of rituximab, a chimeric monoclonal anti-CD20 antibody, affording long disease-free intervals. 5,6 The superior efficacy and reduced therapeutic morbidity, as compared with prior regimens, far outweighs the rare risk of progressive multifocal leukoencephalopathy (2.5 per 100,000).…”
mentioning
confidence: 99%
“…5,6 More recently, disease modulation has been replaced by highly effective disease modification achieved with B-cell depletion through the use of rituximab, a chimeric monoclonal anti-CD20 antibody, affording long disease-free intervals. 5,6 The superior efficacy and reduced therapeutic morbidity, as compared with prior regimens, far outweighs the rare risk of progressive multifocal leukoencephalopathy (2.5 per 100,000). 6,7…”
mentioning
confidence: 99%
See 1 more Smart Citation